2022
DOI: 10.1038/s41598-022-07507-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial occurrence and sources of PAHs in sediments drive the ecological and health risk of Taihu Lake in China

Abstract: To study the spatial occurrence, sources, and ecological risks of 16 PAHs, surface sediments had been collected from seven major areas of Taihu Lake, China in April 2021. Results showed that the concentrations of ∑16PAHs varied between 1381.48 and 4682.16 ng g−1, and the contents of BghiP in each sample were the highest. The PAHs concentrations in the sediments near the lakeshore were much higher than those in the central area of the lake. The sedimentary ∑16PAHs were mainly composed of molecular-weight monome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…However, it could still be concluded that since the 1900s, the PAHs in the sediment core of Taihu Lake mainly came from the combustion of fossil fuels, such as coal and petroleum combustion. This conclusion was also con rmed in previous studies Lang et al 2022). The main source of PAHS in the sediments of the Taihu Lake changed around 1900s, from petroleum to combustion of fossil fuels.…”
Section: Source and In Uencing Factor Identi Cation For Sedimentary P...supporting
confidence: 90%
See 1 more Smart Citation
“…However, it could still be concluded that since the 1900s, the PAHs in the sediment core of Taihu Lake mainly came from the combustion of fossil fuels, such as coal and petroleum combustion. This conclusion was also con rmed in previous studies Lang et al 2022). The main source of PAHS in the sediments of the Taihu Lake changed around 1900s, from petroleum to combustion of fossil fuels.…”
Section: Source and In Uencing Factor Identi Cation For Sedimentary P...supporting
confidence: 90%
“…The molecular diagnostic ratio of PAH was the main method to determine the source of PAHs in samples (Yunker et al 2002;Tobiszewski et al 2012;Lang et al 2022). In this study, Ant/(Ant + Phe), Flu/(Flu + Pyr), BaA/(BaA + Chry) and IcdP/(IcdP + BghiP) were selected to assess the primary source of PAHs.…”
Section: Source and In Uencing Factor Identi Cation For Sedimentary P...mentioning
confidence: 99%
“…Located in China’s most developed eastern region, the Taihu Lake Basin (TLB) covers only 0.4% of China's land but supports 4.4% of its population and contributes 9.7% of its GDP 35 . The high rates of economic development and intensive agricultural activities have accelerated the deterioration of water quality in the area 36 38 . As the lowest part of the basin, Taihu Lake receives a large amount of Nr.…”
Section: Introductionmentioning
confidence: 99%
“…The IcdP concentration accounted for a large proportion of the total PAHs. There is no minimum safe level for IcdP in the environment, and therefore its presence will lead to toxic effects on organisms(Lang et al 2022;Dong et al 2014;Lorgeoux et al 2016). It is therefore recommended to strengthen the monitoring, prevention, and control of IcdP substances in the future and make corresponding emergency plans.…”
mentioning
confidence: 99%